Pelatihan Pembuatan Presentasi Menggunakan Aplikasi Prezi - Meylia Vivi Putri; Agus Suryadi; Eka Lia Febrianti (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2022)
Abstract: This community service aims to optimize students' potential in making presentations. Prezi application that is used to make presentations for students in making presentation materials. the implementation method begins with (1) Introduction: creating a virtual class using google classroom. Then upload applications and materials and register all trainees in the class. The application has been installed before the implementation of the training. Stage (2) Implementation: service is carried out using a zoom meeting which explains the importance of innovation in making presentations. Participants are divided into small groups according to their field, and demonstrate their use using a computer. Each group chooses one material for their presentation. Each group makes a presentation of the material that has been prepared. Each group can be creative with the presenters if they have difficulty. Stage (3) Evaluation: each group presents the material that has been prepared previously. The presenters provide input so that the presentations made can be better. These results train teamwork in producing the best work, train creativity in the use of computer application technology to increase learning creativity, make it easier to see material in one main image.Keywords: Community Service; Prezi; Work Team; SMK Putra Jaya School.Abstrak: Pengabdian kepada masyarakat ini bertujuan untuk mengoptimalkan potensi siswa dalam membuat presentasi. Aplikasi Prezi digunakan untuk membuat presentasi bagi siswa dalam membuat materi presentasi. Metode pelaksanaan diawali dengan (1) Pendahuluan: membuat kelas maya menggunakan google classroom. Kemudian mengunggah aplikasi dan materi serta mendaftarkan semua peserta pelatihan pada classroom tersebut. Aplikasi sudah diinstal sebelum pelaksanaan pelatihan. Tahap (2) Pelaksanaan: pengabdian dilakukan menggunakan zoom meeting yang menjelaskan pentingnya inovasi dalam pembuatan presentasi. Peserta dibagi dalam kelompok kecil sesuai bidangnya, dan mendemonstrasikan penggunaanya menggunakan komputer. Setiap kelompok memilih satu materi ajar untuk dibuatkan presentasinya. Setiap kelompok membuat presentasi dari materi yang telah disiapkan. Setiap kelompok dapat berdiskusi dengan pemateri jika mengalami kesulitan. Tahap (3) Evaluasi: setiap kelompok mempresentasikan materi yang telah disiapkan sebelumnya. Pemateri memberi masukan agar presentasi yang dibuat dapat lebih baik. Hasil pelatihan ini melatih kerja sama tim dalam menghasilkan karya terbaik, melatih kreatifitas dalam penggunakan teknologi aplikasi komputer untuk meningkatkan kreatifitas belajar, memudahkan melihat materi dalam satu gambar utama.Kata kunci: Pengabdian Masyarakat; Prezi; Tim Kerja; SMK Putra Jaya School.